The role of usability in the technology acceptance of projection-based user-interfaces - Çinar, Ece; Alppay, Ekrem Cem (Istanbul Teknik Universitesi, Faculty of Architecture, 2023)
This paper aims to discover the role of usability on the technology acceptance of projection-based user-interfaces in the kitchen context. VUX–Virtual User Experience; a system consisting of a hob, a hood and a dishwasher machine controlled by a projection-based user-interface, was chosen as the product. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was chosen as the theoretical frame. A two-phase study was conducted with 30 participants based on the functional prototype. The first phase consisted of a structured user-test in a showroom kitchen environment in which participants were requested to complete pre-defined tasks. The second phase was a UTAUT questionnaire including 32 questions organized in 9 sections. Content analysis and statistical analysis were used to analyze qualitative and quantitative data from the UTAUT questionnaire. It has been found that although the projection-based user-interface has a great role on technology acceptance based on usability, most of the users defined their behavioral intention to use VUX by their attitude toward using technology, experience, and anxiety in the kitchen context. In terms of user-interface design, it has been found that the design characteristics of the user-interface, such as form of icons, color and shape, did not have a significant effect on the technology acceptance of VUX. In terms of usability, errors and safety concerns were found to be the most effective factors in the acceptance of technology by determining the usability of the system. © 2023 Elsevier B.V., All rights reserved.
Keywords: Projection-based user-interface; Technology-acceptance; Usability; User-interface design